Women in the Movement: The Role of Barkah Al Ganis Al Nahdi in PAI Istri (1940–1942) - Diki Tri Apriansyah Putra; Lobelia Asmaul Husna; Nur Fajar Absor; Fikri Akbar, M.; Maisarah, Maisarah (Al Huwiyah: Journal of Woman and Children Studies, 2025)
This research examines the role of Barkah Al Ganis Al Nahdi within PAI Istri (the women’s branch of the Persatuan Arab Indonesia) during the years 1940–1942. Coming from an Arab-Indonesian community that remained deeply rooted in patriarchal traditions, Barkah’s activism is particularly significant as she succeeded in encouraging women’s awareness and participation in public life, especially in relation to education and social rights. The research employs a historical approach with qualitative methods, drawing on primary sources such as archival records, colonial and PAI-affiliated newspapers and magazines, interviews with family members, and organizational documents. The findings reveal that Barkah was not only an active member of the association but also played a role in broadening the discourse of emancipation among Hadrami-Indonesian women, despite the restrictive social and political circumstances of the time. Her efforts illustrate that women’s struggles were not always overtly confrontational but could also unfold gradually and strategically from within their own communities. Keywords: PAI Istri, Barkah Al Ganis, Arab-Indonesian women, emancipation, women’s history.